TELESEISMIC TOMOGRAPHY REVEALS NO SIGNATURE OF THE DEAD SEA TRANSFORM IN THE UPPER MANTLE STRUCTURE - Koulakov I.; Sobolev S.V.; Weber M.; Wylegalla K.; Oreshin S.; Hofstetter R. (My University, 2006)
We present results of a tomographic inversion of teleseismic data recorded at 48 stations of a temporary network which was installed in the area of the Dead Sea Transform (DST) and operated for 1 yr in the framework of the multidisciplinary DESERT Project. The 3366 teleseismic P and PKP phases from 135 events were hand picked and corrected for surface topography and crustal thickness. The inversion shows pronounced low-velocity anomalies in the crust, beneath the DST, which are consistent with recent results from local-source tomography. These anomalies are likely related to the young sediments and fractured rocks in the fault zone. The deeper the retrieved anomalies are quite weak. Most prominent is the high-velocity strip-like anomaly striking SE-NW. We attribute this anomaly to the inherited heterogeneity of lithospheric structure, with a possible contribution by the shallow Precambrian basement east of the DST and to lower crustal heterogeneity reported in this region by other seismic studies. We do not observe reliable signature of the DST in the upper mantle structure. Some weak indications of low-velocity anomalies in the upper mantle beneath the DST may well result from the down-smearing of the strong upper crustal anomalies. We also see very little topography of the lithosphere-asthenosphere boundary beneath the DST, which would generate significant horizontal velocity variations. These results are consistent with predictions from a recent thermo-mechanical model of the DST. Our tomographic model provides some indication of hot mantle flow from the deeper upper mantle rooted in the region of the Red Sea. However, resolution tests show that this anomaly may well be beyond resolution of the model. © 2006 Elsevier B.V. All rights reserved.
Keywords: ASTHENOSPHERE; DEAD SEA TRANSFORM; LITHOSPHERE; TECTONOPHYSICS; TELESEISMIC TOMOGRAPHY; Палеозой::Кембрийская; Докембрий; Paleozoic::Cambrian; Precambrian